Forage seed production, processing and handling in Ethiopia - Bezabih, Melkamu; Habte, Ermias; Adie, Aberra (International Livestock Research Institute, 2025)
Livestock are central to the livelihoods and economies of most African countries. The dominant production systems (mixed crop-livestock, pastoral, and agropastoral) depend heavily on feed resources, which represent the largest cost in livestock production. However, inadequate feed quantity and quality remain major constraints to productivity. Recurrent droughts and land degradation further worsen feed scarcity, increasing the vulnerability of smallholder systems.